Laser-Induced Color Marking of Titanium Alloy - Li Chunling; Lu Changhou (Universitas Ahmad Dahlan, 2016)
A Nd:YAG nanosecond laser was utilized in the laser color marking of titanium alloy substrates. It was focused on how several laser parameters, such as pumping current, delay between the effective vector step, laser line spacing, Q-switch frequency and focal plane offset, affected the resulting colors, and the influence of the resulting colors on the substrate. Firstly, single-factor experiments were carried out. Then the dark blue square pattern and two samples were analyzed using an environmental scanning electron microscope (ESEM) and X-ray diffractometer (XRD) respectively. Results clearly showed that the Nd:YAG nanosecond laser can induce multiple colors on titanium alloy substrates and all the five parameters had an effect on the resulting colors significantly. The dark blue square pattern didn’t induce internal stresses within the substrate material, so the influence of the resulting colors on the substrate is negligible.